Pengaruh Kualitas Terhadap Kepuasan Pelanggan Bus Jurusan Samarinda Bontang Pada Terminal Lempake Di Kota Samarinda - AL Halim (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The purpose of this study is to test the Quality of Service on Customer Satisfaction. The population in this study were 96 passengers on the bus of Samarinda Bontang Department at Lempake Terminal in Samarinda City. The variables used in this study consisted of the independent variable, namely the Service Quality variable (X), and the dependent variable, namely Customer Satisfaction (Y). The results of the analysis using simple regression analysis. Data collection techniques are based on the source, including primary data through observation, interviews, questionnaires or questionnaires, and include documentation. Secondary data, among others, by searching for literature in the form of previous research journals, and textbooks that are related to the variables to be studied. The data analysis technique used the validity test and reliability test. Whereas for the data analysis technique method using the Determination Analysis method, hypothesis testing using the t test. The results show that the Service Quality (X) variable simultaneously has a significant effect on Customer Satisfaction (Y) Buses in Samarinda Bontang Department at Lempake Terminal in Samarinda City.